Analisis Pembelajaran Tematik Integratif Pada Siswa Kelas V SDN Talabiu Kabupaten Bima - Suciyati Suciyati (Pusat riset dan Inovasi Nasional, 2023)
The purpose of this research is to describe the integrative thematic learning process for fifth grade students. The method used in this study is qualitative. Data collection techniques using interviews and observation and analyzed based on reduction diagrams, interpretation and conclusion. Research results at the learning planning stage, some lesson plans have used thematic lesson plans, but there are some subject matter that have not used thematic lesson plans. At the small part of the learning implementation stage, the delivery of material has not used thematic learning models, as seen in the delivery of material still based on subjects. Most of them already use thematic learning models. Furthermore, at the assessment stage, the thematic assessment model has not been used. The assessment of learning outcomes carried out by all teachers is in the form of a written test which is still carried out based on the subject. The obstacles to the application of thematic learning, namely the lack of socialization regarding thematic learning and the limitations of adequate teaching aids, so that it is less than optimal in concrete learning